Sexual abuse : beauty for ashes - Kellemen, Robert W. (Phillipsburg, New Jersey : P&R Publishing, 2013)
From disgrace to grace and from victims to victors. Sexual abuse ravages the soul, causing unimaginable distress, damage, and disgrace. It is faced honestly and openly in the Bible -- but can the church truly help those who have been sexually abused? Bob Kellemen says yes, it can; and using the biblical story of Amnon and Tamar, he realistically portrays the damages wrought by sexual abuse and the relevancy of God's Word to this difficult topic. He then takes us on a journey toward healing, helping sufferers to reclaim beauty from the ashes of abuse and to move from victim to victor. The Gospel for Real Life booklet series by the Association of Biblical Counselors (ABC) applies the timeless hope of Christ to the unique struggles of modern believers. - Back cover.
Grace for our disgrace -- God's central message to you. God's mission statement -- The central message of life and of ministry -- The central message of 2 Samuel 9 to 1 Kings 2 -- Understanding the damage done by sexual abuse : 2 Samuel 13. Why examine the damage done? -- Our journey in : compass points of the soul. Journey one : the damage of loss of trust : the attempted destruction of faith (2 Sam. 13:1-12) -- Journey two : the damage of powerlessness : the attempted destruction of hope (2 Sam. 13:2, 11-14) -- Journey three : the damage of shame : the attempted destruction of peace/shalom (2 Sam. 13:13-17) -- Journey four : the damage of being used and feeling useless : the attempted destruction of love (2 Sam. 13:14-20) -- Painting portraits of the damage done. The loss of faith : the door of the heart bolted shut -- The loss of hope : the death of dreams -- The loss of peace : the downcast eyes -- The loss of love : the torn robes of the King's child -- From victim to victor in Christ : beauty for ashes -- The journey out : the pathway to God's healing hope. Sustaining : it's normal to hurt -- Healing : it's possible to hope -- Reconciling : it's horrible to sin, but wonderful to be forgiven -- Guiding : it's supernatural to mature -- Keep clinging to Christ -- Applying the gospel to daily life.
Includes bibliographical references.
Keywords: Sexual abuse victims -- Religious life; Abused women -- Religious life; Sex crimes -- Religious aspects -- Christianity; Bible -- Criticism, interpretation, etc